Mumps transmission in social networks: a cohort study. Issue 1 (December 2017) - Hahné, Susan; Schurink, Tessa; Wallinga, Jacco; Kerkhof, Jeroen; van der Sande, Marianne; van Binnendijk, Rob; de Melker, Hester
Abstract Background Mumps emerged among highly vaccinated populations in the Netherlands. This offered a unique opportunity to study mumps virus transmission. In particular the extent to which asymptomatic infections in vaccinated people contribute to ongoing mumps virus transmission is uncertain. Insight into this could help project the future burden of mumps in vaccinated populations. We therefore studied the relative infectiousness of symptomatic and asymptomatic cases. Methods In a cohort study we followed contacts of notified mumps cases (ring 1) and contacts' contacts (ring 2) for 40 days to ascertain symptoms of mumps and social contacts by weekly diaries and questionnaires, and mumps virus infections by taking finger stick dried blood spot specimens (DBS) that were tested for mumps-specific IgG antibodies. Mumps IgG concentrations >1500 RU/ml in a single sample, a four-fold increase in IgG antibody concentration in paired samples, or a positive oral fluid PCR were defined as recent infection. Results We recruited 99 contacts (40 in ring 1 and 59 in ring 2) of 10 mumps index cases. The median age of participants was 23 years (range 18–57 years), 31 (31%) were male. At study entry, DBS of 4 out of 78 (5%) participants with samples showed serological evidence of recent mumps virus infection. Three of these reported mumps symptoms. Among the 59 participants who provided DBS at the beginning and end of the follow-up period, none had serological evidence of infection during this period. Of 72 participants who provided at least one oral fluid sample, one participant (1%) who also reported mumps symptoms, was found PCR positive. Of all 99 participants, the attack rate of self-reported mumps was 4% (95% CI 1.1–10.0%). Of the 5 laboratory confirmed mumps cases, 1 reported no mumps symptoms (percentage asymptomatic 20% (95% CI 0–71%)). Compared to non-students, students had larger households and more household members who were born after 1980 (p  < 0.01 and <0.01, respectively). Conclusions We demonstrated that this prospective cohort study design allows for inference of the proportion of asymptomatic mumps infections. Because we only detected one asymptomatic mumps virus infection, we could not assess the relative infectiousness of asymptomatic mumps. Household characteristics of students differed from non-students. This may partly explain recent mumps epidemiology in the Netherlands.